2019
DOI: 10.33225/jbse/19.18.549
|View full text |Cite
|
Sign up to set email alerts
|

Examining Secondary School Students’ Misconceptions About the Human Body: Correlations Between the Methods of Drawing and Open-Ended Questions

Abstract: Students of various age groups manifest numerous explanations that differ from what is known to be scientifically correct. Misconceptions about the human body are one of the best studied areas of students’ understanding of scientific phenomena. To explore misconceptions, researchers have at their disposal various methods which can lead to different results. In order to find an effective, cheap and representative diagnostic instrument, correlations between scores obtained by open-ended questions and drawings on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
10
1
Order By: Relevance
“…Another objective of the research was to identify whether the alternative conceptions about functional aspects related to human nutrition, which have been relatively well documented in children (Carvalho et al, 2004;Dempster & Stears, 2014;García-Barros et al, 2011;López-Manjón & Postigo, 2009;Teixeira, 2000), are also present among the students. The results of the present research showed that the most common mistakes were related to the urinary system, demonstrating the close relation between the drawings and the written answers, in contrast to previous reports (Fančovičová & Prokop, 2019;Prokop & Fančovičová, 2006). The pre-service teachers confused the urinary system with the digestive system and believed that some organs of the digestive system such as the intestines or pancreas were part of the urinary system.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Another objective of the research was to identify whether the alternative conceptions about functional aspects related to human nutrition, which have been relatively well documented in children (Carvalho et al, 2004;Dempster & Stears, 2014;García-Barros et al, 2011;López-Manjón & Postigo, 2009;Teixeira, 2000), are also present among the students. The results of the present research showed that the most common mistakes were related to the urinary system, demonstrating the close relation between the drawings and the written answers, in contrast to previous reports (Fančovičová & Prokop, 2019;Prokop & Fančovičová, 2006). The pre-service teachers confused the urinary system with the digestive system and believed that some organs of the digestive system such as the intestines or pancreas were part of the urinary system.…”
Section: Discussioncontrasting
confidence: 82%
“…Numerous studies have been undertaken to determine the conceptual understanding that students have of the human body's functions and structure (Bahar et al 2008;Carvalho et al, 2004;Cuthbert, 2000;Fančovičová & Prokop, 2019;García-Barros et al, 2011;Manokore & Reiss 2003;Prokop et al 2009;Reiss & Tunnicliffe, 2001;Reiss et al, 2002;Rowlands, 2004;. Although different techniques have been used (surveys, questionnaires, two-tier diagnostic tests, interviews, etc.…”
Section: Human Body Knowledge Using Drawings As a Methods Of Conceptuamentioning
confidence: 99%
“…Open‐ended responses were scored by their respective rubric and closed‐ended responses were scored in a binary fashion (in/correct). The drawing (question 1) and tracing (question 30) items are particularly useful assessments to illuminate students' respective external and internal anatomical misconceptions (Reiss et al, 2002), especially those of the heart (Fančovičová & Prokop, 2019). Further, both the drawing and labelling of the heart (of question 1, at the macro‐level) and tracing of pulmonary circulation (question 30, at the micro‐level) provided greater visualization to how students are constructing knowledge from use of the technology, among a large sampling of students (Gurel et al, 2015) in both form and function and systems thinking.…”
Section: Methodsmentioning
confidence: 99%
“…[181] body systems (Fančovičová & Prokop, 2019;Çuçin, Özgür, & Güngör-Cabbar, 2020), enzymes (Bretz & Linenberger, 2012; and genetics (Gül & Özay-Köse, 2018b;Shaw, Horne, Zhang, & Boughman, 2008). It was also revealed that they have misunderstandings and misconceptions on these issues.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…These studies interpreted the findings that biology is considered hard by students because it contains many abstract concepts. Thus, this situation causes students to have learning difficulties that also result in many misunderstandings and misconceptions (Adıgüzel, & Yılmaz, 2020;Elmesky, 2013;Erdoğan-Karaş & Gül, 2020;Fančovičová, & Prokop, 2019;Rogayan, & Albino, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%